Disentangling the Deformation Process of Earthen Sites and Understanding the Role of Na2SO4 and Precipitation: A Case Study on the Great Wall Relics of the Ming Dynasty in Yulin, China. (2nd January 2021) - Mao, Weijia; Shen, Yunxia; Zhu, Yingpei; Bai, Yunfeng; Sun, Manli
ABSTRACT: Earthen sites in China have great historic, artistic, and scientific values embedded in archaeology, raw materials, and construction techniques. However, high concentrations of salt could potentially cause severe deformation to these earthen sites, and heavy local precipitation can greatly facilitate the process of dissolution and recrystallization of salt. In this study, environment-simulated experiments are conducted to further understand the process and characteristics of this deformation. Deterioration experiments show that soil samples with low salt content are subjected to a variety of deformations, including cracks and collapses as well as basal corrosion on the surface, whereas those containing higher salts show other deformation forms, surface peeling, and basal corrosion. Intriguingly, higher salt concentration leads to relatively smaller soil volume expansion. We conducted more observations and analyses to reveal the underlying mechanism. Results show that high-content salt will clog capillary pores and make pore size smaller and cause concentration and encrustation of salt on the outer surfaces of soil, which, to a certain extent, blocks water absorption of soil under the influence of rain. Therefore, the degree of soil expansion declines, and the types of soil deterioration change. Nevertheless, further work should be done to reveal the contribution of clay minerals on salty soil swelling. Better understanding of the underlying deterioration mechanism can be helpful in designing more specific preservation strategies for these invaluable earthen sites in the near future.